(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Today, preschool education organizations have the main goal of comprehensively preparing children for school and harmonious development. In order to improve the quality of preschool education, it is necessary to prepare the child for school from an early age, the integrated formation of basic competencies, a modern approach to pedagogical and psychological processes.